Culture-Led Urban Regeneration: How Does Melukis Harapan Catalyst The Transformation of Dolly Prostitution District? - Hanif Azhar (Journal of Governance and Social Policy, 2021)
The position of cultural regeneration to develop social and economic growth in a post-black economy district like a former sex leisure business is becoming a thought-provoking investigation. This research focuses on a specific observation to find the relationship between regeneration and former prostitution in culture-led urban reinforcement to develop through the creative industry? What are the influences behind the rise of culture-led borough redevelopment in such a place of ex-prostitution? This research used the post-positivism paradigm with qualitative method approach. Some of the opinions behind the growth of culture-led urban regeneration have linked not only in cultural icon and urban identity but also in community consolidation to support the creative industry elaboration. Further, the products of culture-led urban renewal, we can say youth movements, has the assumption to potentially advance the local cultural policy discourses within creative industry outcome. This research presents the effect of accepted place in Dolly, the ex-biggest well-organized prostitution in southeast Asia located in Surabaya, Indonesia. It implication is to show the result of observations and experiences conducted with the local youth community, Melukis Harapan, as a cultural flagship development subject that successfully transform Dolly into an education-tourism-based creative village.